Evaluation of Point-of-Care Testing in Pharmacy to Inform Policy Writing by the New Brunswick College of Pharmacists - Lauren Hutchings; Anastasia Shiamptanis (MDPI AG, 2022)
Pharmacy practice continues to advance, allowing professionals to contribute further to patient care and the healthcare system. Pharmacists are authorized to perform point-of-care testing (POCT) in seven out of ten Canadian provinces. In considering the potential for enhanced clinical decision-making with the opportunity to gain patient data at the site of care, the New Brunswick College of Pharmacists (NBCP) proceeded to draft regulatory amendments and a policy to enable POCT scope in New Brunswick. Policy writing is a core function of Provincial Regulatory Authorities in Canada as the process determines principles that direct pharmacy practice. Each province has a differing scope of practice and method for developing documents. This paper highlights the approach, analysis, and findings of the NBCP pursuant to drafting a POCT policy. The policy development process included a literature search and environmental scan of the ten Canadian provincial regulatory authorities along with other countries. The findings highlighted in this paper describe the use of POCT, quality assurance, regulatory framework, educational opportunities, and the role of pharmacy technicians in relation to POCT in a pharmacy setting. The approach NBCP took to engage professionals and decisions on the direction of the policy are described. As point-of-care services continue to expand in pharmacies, the insights by the NBCP can be utilized by other regulatory bodies or pharmacy professionals who are implementing or enhancing POCT policies or procedures within their organizations.